Is avoidable diabetes-related hospitalization in older patients with type 2 diabetes mellitus associated with increased health expenditure?: A nationwide retrospective cohort study in South Korea - Woo-Ri Lee; Gyeong-Min Lee; Noorhee Son; Kyu-Tae Han; Sungyoun Chun; Yehrhee Son; Ki-Bong Yoo (Preventive Medicine Reports)
Objective: With South Korea's population aging rapidly, the number of patients with type 2 diabetes mellitus (T2DM) is expected to rise, leading to worsened health outcomes and potentially straining healthcare financing. This study aimed to investigate how avoidable diabetes-related hospitalizations affect short- and long-term health expenditures. Methods: Data from the National Health Insurance Service-Senior cohort from 2008 to 2019 in South Korea. A total of 27,081 participants aged 60 years and older who were diagnosed with T2DM were included in the study. The independent variable in this study was avoidable diabetes-related hospitalization according to the ICD-10 criteria “E11”. The outcome measures included one- and five-year health expenditures. Regression analysis was performed using the generalized estimating equation (GEE) with a gamma distribution and log-link function. Inverse Probability of Treatment Weighting (IPTW) analysis was conducted to enhance the robustness of the results. Results: Out of the 27,081 participants, 685 patients (2.5 %) experienced avoidable diabetes-related hospitalizations. GEE analysis with IPTW weights revealed that participants who experienced avoidable hospitalizations had a higher risk of increased health expenditures (one-year: relative risk (RR) 1.83, 95 % CI 1.76–1.91; five-year: RR 1.63, 95 % CI 1.57–1.69). Consistent patterns were observed even without weighting (one-year: RR 1.85, 95 % CI 1.68–2.04; five-year: RR 1.60, 95 % CI 1.47–1.74). Conclusions: Our findings highlight the importance of continuous health management to prevent avoidable hospitalization, thereby promoting health and ensuring the financial stability of older patients with T2DM within the healthcare insurance system.